Optimal fiscal policy rule for achieving fiscal sustainability: A Japanese case study - Naoyuki Yoshino; Tetsuro Mizoguchi; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2015)
Japan's debt-to-gross domestic product (GDP) ratio is the highest among Organisation for Economic Co-operation and Development (OECD) countries. This paper will firstly answer the question of whether Japanese government debt is sustainable. Next, while the Domar condition and Bohn's condition are often used in the literature to check whether a government's debt situation is in a dangerous zone, this paper will show that the Domar condition is obtained only from the government budget constraint (namely the supply of government bonds) and does not take into account the demand for government bonds. A simple comparison of the interest rate and the growth rate of an economy using the Domar condition is not adequate to check the stability of a government's budget deficit. Both the interest rate and the growth rate of the economy are determined endogenously in the model. Thirdly, this paper shows that Bohn's condition satisfies the stability of the government budget in the long run by imposing constraints on the primary balance. However, Bohn's condition does not achieve economic stability - even if the condition is satisfied, the recovery of the economy may not be achieved. This paper will propose a new condition that satisfies both the stability of the government budget and the recovery of the economy. The paper will shed light on these issues both theoretically and empirically. The empirical findings declare that in order to achieve fiscal sustainability based on the optimal fiscal policy rule provided in this paper, both sides of the Japanese government budget (expenditure and revenue) need to be adjusted simultaneously. Moreover, the results show that the decrease in government expenditure has to be to more than the increase in tax revenue.
Keywords: E42; E63; 330; fiscal policy; fiscal sustainability; Domar condition; Bohn's condition; fiscal policy rule